2005
DOI: 10.5194/angeo-23-2961-2005
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study on the correlations between plasma sheet and solar wind based on DSP explorations

Abstract: Abstract. By using the data of two spacecraft, TC-1 and ACE (Advanced Composition Explorer), a statistical study on the correlations between plasma sheet and solar wind has been carried out. The results obtained show that the plasma sheet at geocentric distances of about 9∼13.4 Re has an apparent driving relationship with the solar wind. It is found that (1) there is a positive correlation between the duskward component of the interplanetary magnetic field (IMF) and the duskward component of the geomagnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
10
3
Order By: Relevance
“…The results revealed that the particle pressure and the total pressure of the plasma sheet are strongly correlated with the ram pressure of the solar wind, with coefficients of 0.84 and 0.85, respectively. Recently, Double Star (TC‐1) observations [ Yan et al , 2005] also reported the same results, showing that the solar wind dynamic pressure significantly controls the ion thermal pressure in the near‐earth plasma sheet. Note that their studies did not consider the ion species.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The results revealed that the particle pressure and the total pressure of the plasma sheet are strongly correlated with the ram pressure of the solar wind, with coefficients of 0.84 and 0.85, respectively. Recently, Double Star (TC‐1) observations [ Yan et al , 2005] also reported the same results, showing that the solar wind dynamic pressure significantly controls the ion thermal pressure in the near‐earth plasma sheet. Note that their studies did not consider the ion species.…”
Section: Discussionmentioning
confidence: 63%
“…In the previous studies, the following two processes have been considered as mechanisms for changing the ion population in the magnetosphere. One is that solar wind conditions control the variation of the plasma sheet properties [ Borovsky et al , 1998; Thomsen et al , 1998; Yan et al , 2005], and another is that solar wind conditions control the ionospheric ion outflow [ Moore et al , 1999; Elliott et al , 2001; Cully et al , 2003]. Borovsky et al [1998] statistically studied the coupling of the plasma sheet to the solar wind using the ISEE‐2 data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Faganello et al [2012] showed another type of the vortex-induced reconnection in 3-D. Hasegawa et al [2009] revisited the Cluster event of rolled-up K-H vortices shown in Hasegawa et al [2004] and found the evidence of the associated reconnection near the rolled-up interval. Some models or statistical studies presented that during northward IMF, the solar wind could be transported into magnetosphere through the LLBL caused by the KHI [Fujimoto et al, 1997;Fairfield et al, 2000;Tsyganenko and Mukai, 2003;Yan et al, 2005]. As for the single point observation of rolled-up vortices, the criteria were established [Hasegawa et al, 2006] to identify the rolled-up K-H vortices and the solar wind entry into the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Regression models parameterized by B Y in addition to AE 3.5 or [dΦ MP /d t ] 5.0 , calculated separately for each hemisphere, do not perform any better. Although this is not the case for the polar cap or other precipitation boundaries, and the convection pattern in general, the equatorward edge of electron precipitation does not appear to vary with B Y , despite the influence B Y has on the inner magnetosphere (e.g., Matsui et al, ; Yan et al, ). This was confirmed through manual inspection of data plots similar to Figure , as well as the diminished efficacy of models parameterized by (AE, B Y ) and (dΦ MP /d t , B Y ) shown in Table , regardless of the parameters used in the weighted average of B Y .…”
Section: Resultsmentioning
confidence: 96%